Effects of heat waves on heat stroke in Shanghai, 2013—2023 - Fei’er CHEN; Chunyang DONG; Jianghua ZHANG; Hailei QIAN; Zheng WU; Yewen SHI; Xiaodong SUN (环境与职业医学, 2024)
BackgroundThe substantial health damage attributed to heat waves, along with their increasing intensity and frequency in the context of global warming, highlights the importance of exploring the health effects of heat waves. ObjectiveTo calculate the excess heat stroke cases during heat waves in the summer of 2013—2023 in Shanghai, analyze the association between heat waves and heat stroke, and to further explore the modifying effects of heat wave characteristics on heat stroke. MethodsUsing a retrospective ecological study design, data on heat stroke cases were collected from the heat stroke case reporting system of the Chinese Center for Disease Control and Prevention, and concurrent meteorological data from Xujiahui Meteorological Station. A heat wave was defined as at least 3 consecutive days with daily maximum temperature meeting or exceeding 35 ℃ in this study, excess heat stroke cases related to heat waves were assessed as the difference between the numbers of heat stroke cases observed on a given day and the corresponding 31 d (15 d before and after that day) moving average, and statistical analyses using generalized linear model based on time series study were performed to assess the impact of heat waves on heat stroke. ResultsOverall 25 heat waves during the study period were observed, leading to a total of estimated 792.6 extra heat stroke cases. The risk of heat stroke significantly increased during heat waves (RR=2.60, 95%CI: 2.08, 3.26), but no statistically significant differences in heat wave effects were observed among different genders, ages, or regions. In terms of the timing of heat waves, the risk of heat stroke was highest during the first heat wave (RR=3.58, 95%CI: 2.82, 4.55), which was significantly higher than that during the second heat wave (RR=2.19, 95%CI: 1.66, 2.90), and no significant effect was observed during the third or subsequent heat waves. The impact of heat waves on heat stroke persisted for more than 4 d, with the risk higher on the fourth day and beyond (RR=2.95, 95%CI: 2.28, 3.83), significantly higher than on the first day of heat wave (RR=1.74, 95%CI: 1.18, 2.56). ConclusionHeat waves had a substantial effect on heat stroke in Shanghai from 2013 to 2023, and special attention need to be paid to heat waves with early onset and long duration.